The Implementation Of Ui/Ux (User Interface/User Experience) For Improving Educational Websites: Case Study At Sma Negeri 1 Central Bengkulu - Armeliansyah, Yadi; Aspriyono , Hari; Farisy , Ahmad Arib Al (Jurnal Komputer Indonesia, 2025)
Advances in information technology have encouraged educational institutions to improve their digital services, including through educational websites. SMA Negeri 1 Cental Bengkulu already has an official website, but there are still issues with its appearance and user experience. This study aims to implement UI/UX to improve the appearance and user experience of the website to make it more informative, accessible, and attractive. The approach used is qualitative with the Design Thinking method through the stages of problem identification, wireframe design, prototyping, and testing. The design developed also accommodates the needs of users from students, teachers, and parents. The writer’s suggestion is that the implementation of UI/UX be applied comprehensively as a more effective medium for information and learning at SMA Negeri 1 Central Bengkulu.